Spontaneous decision-making behavior: correlation of electrodermal activities to an architecture design time-problem - Saxena, Ashish; Khare, Rachna (International journal of technology and design education, 2025)
Spontaneous judgment and decision-making (JDM) are common behaviors that remain ambiguous to be utilized in architecture design studios. A decision-maker (DM) response varies due to individual differences in an architectural design (AD) environment that keeps changing from abstract ideas to concrete design details along the process. The study aims to improve understanding of spontaneous decision-making behaviors based on individual differences during the AD process. Intuitive and deliberate decision-makers ( n = 36) identified based on the PID (preference for intuition and deliberation) scale participated as novice (second year) and expert (fourth year) groups of AD students. Electrodermal activity (EDA) was measured along self-assessment during a three-stage time problem of the stratified groups, i.e., deliberate novice (ND), intuitive novice (NI), deliberate expert (ED), and intuitive expert (EI) decision-makers. Differences in physiological changes were observed concerning the stages of AD problem among DM groups. Lesser deviation of EDA was observed among the deliberate style of DMs than the intuitive style. The average EDA of novices peaked during the start whereas the same was found to rise at the end in the case of experts during the time problem. The study discusses individual differences in conditions of spontaneous decision-making behaviors during the AD process based on physiological activation in a time-pressured condition. The study approaches individual differences in design decision-making behaviors from a combined aspect of subject expertise and trait-based conditions along the AD process. It highlights the importance of EDA in future research providing cognitive insights about DM’s behaviors applicable to design thinking and pedagogy.